A systematic course in the ancient tantric techniques of yoga and kriya a book of inner awakening - Saraswati, Swami Satyananda (Munger Yoga Publications Trust, 1981)
This book is the most comprehensive text ever published on yoga. It contains a complete course of 36 structured lessons on all the practices of integral yoga. The lessons were compiled from the teachings given by Swami Satyananda Saraswati and are useful as a practical and theoratical guide for all levels of yoga teachers and aspirants. This book presents a synthesis of yoga in a scientific and systematic manner. The different branches of hatha yoga, raja yoga, mantra yoga, karma yoga, bhakti yoga, jnana yoga and kriya yoga ar progressively introduced with special emphasis on practice, theory and application in daily life. About the Author(s) Swami Satyananda was born at Almora, Uttar Pradesh, in 1923. In 1923 he met Swami Sivananda in Rishikesh and adopted the Dashnami sannyasa way of life. In 1955 he left his guru's ashram to life as a wandering mendicant and later founded the International Yoga Fellowship in 1956 and the Bihar School of Yoga in 1963. Over the next 20 years Swami Satyananda toured internationally and authored over 80 books.
Keywords: Yoga; Yoga, Kriya; Tantrism; Hatha yoga